Doped metal oxide for dielectric applications - Gadtya, Ankita Subhrasmita; Satpathy, Santosh Kumar; Moharana, Srikanta; Yakuphanoğlu, Fahrettin (Elsevier, 2025)
Metal oxide materials doped with various elements have emerged as promising candidates for advanced dielectric applications due to their tunable electrical properties, enhanced electrical properties, and high charge storage capabilities. These modified oxide systems demonstrate superior dielectric constants, reduced loss factors, and improved temperature stability compared to their undoped counterparts. The precise control of dopant concentration and distribution, made possible by recent developments, has optimized dielectric behavior for particular applications, such as microelectronic devices and capacitors. Metal oxide systems with remarkable dielectric qualities and good mechanical stability and dependability have been successfully engineered through careful dopant element and processing condition selection. These developments have opened new possibilities for next-generation electronic components and energy storage devices. This chapter provides an overview of the recent advancements of doped metal oxides in dielectric devices, highlighting their superior performance to traditional dielectric materials. © 2026 Elsevier Inc. All rights reserved.
Keywords: Dielectric loss; Dielectric properties; Dopant materials; Metal oxides; Microstructural engineering